Hadis sebagai Sumber Hukum Islam - Abu Azam Al Hadi (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2020)
Hadith as the basis of Islamic law does not consist of all forms of hadith, even though its veracity has been shown by the Koran. The scholars' from among Muhaddithin, Usuliyyin, and Fuqaha', have formulated the basics of hadith hujjahan, namely al-hadith al-maqbulah (hadith accepted as a source of Islamic law) and al-hadith al-mardudah (a hadith that is rejected as a source of Islamic law). According to them, the hadith of al-Maqbul must be based on the principle of rejecting or accepting a hadith narration, that is, it must be narrated by a narrator who is 'adil and dabit, and in that hadith status there is no' illah al-qadihah (severe disability) and the narrator does not experience shudud (peculiar). Muhaddithi n takes the stance to accept all hadiths, both sahih, hasan and da'if to be practiced, except in a position that is not too weak (da'if). But that is not the attitude of Usuliyyin ', and Fuqaha', they took the basis of istinbat to the hadith that has the value of sahih or hasan which are both ma'mul bih (which can practice), although al-hadi th ghayr al-mutawatirah (a hadith not narrated by many narrators) and give benefits yaqin, and if ghayr ma'mul bih (cannot be practiced), then according to they are rejected as the basis of legal terms.